Acute Diuretic-Sparing Effects of Sacubitril-Valsartan: Staying in the Loop. (December 2022) - Orvin, Nicholas J.; Beavers, Janna C.; Russell, Stuart D.
Background: Previous literature has suggested a potential diuretic sparing effect as early as 6 months following sacubitril-valsartan initiation in patients with heart failure with reduced ejection fraction (HFrEF); however, whether this effect manifests earlier after initiation is unclear. Objective: To evaluate the acute diuretic-sparing effects of sacubitril-valsartan. Methods: This was a single-center, retrospective analysis of outpatients with HFrEF initiated on sacubitril-valsartan with follow up within 90 ± 30 days and a concomitant loop diuretic prescription. The primary outcome was the percent of patients with an increase, decrease or no change in loop diuretic total daily dose (TDD). Key secondary outcomes included change in loop diuretic TDD (mg furosemide equivalents) and hospital admissions or emergency department (ED) visits. Results: A total of 145 patients were included (overall cohort) with 120 continuing sacubitril-valsartan at follow up (on-treatment cohort). In the on-treatment cohort, 20% (n = 24) had a reduction in loop diuretic TDD and 10% had an increase (n = 12). Median change in loop diuretic TDD was unchanged from baseline to follow up (p 0.13). In patients on >80 mg TDD of furosemide at baseline (n = 9), mean change was-53 ± 44 mg (p 0.006). Hospitalizations (6.2%) and ED visits (0.7%) for heart failure were infrequent. Conclusion: Patients may require a loop diuretic dose reduction within 2-3 months following sacubitril-valsartan initiation. This diuretic-sparing effect appears larger in those on higher baseline loop diuretic doses, and closer follow up may be warranted for these patients.